Biventricular Increases in Mitochondrial Fission Mediator (MiD51) and Proglycolytic Pyruvate Kinase (PKM2) Isoform in Experimental Group 2 Pulmonary Hypertension-Novel Mitochondrial Abnormalities - Xiong, Ping Yu; Tian, Lian; Dunham-Snary, Kimberly J.; Chen, Kuang-Hueih; Mewburn, Jeffrey D.; Neuber-Hess, Monica; Martin, Ashley; Dasgupta, Asish; Potus, Francois; Archer, Stephen L. (Frontiers in Cardiovascular Medicine, 2019)
Introduction: Group 2 pulmonary hypertension (PH), defined as a mean pulmonary arterial pressure ≥25 mmHg with elevated pulmonary capillary wedge pressure >15 mmHg, has no approved therapy and patients often die from right ventricular failure (RVF). Alterations in mitochondrial metabolism, notably impaired glucose oxidation, and increased mitochondrial fission, contribute to right ventricle (RV) dysfunction in PH. We hypothesized that the impairment of RV and left ventricular (LV) function in group 2 PH results in part from a proglycolytic isoform switch from pyruvate kinase muscle (PKM) isoform 1 to 2 and from increased mitochondrial fission, due either to upregulation of expression of dynamin-related protein 1 (Drp1) or its binding partners, mitochondrial dynamics protein of 49 or 51 kDa (MiD49 or 51). Methods and Results: Group 2 PH was induced by supra-coronary aortic banding (SAB) in 5-week old male Sprague Dawley rats. Four weeks post SAB, echocardiography showed marked reduction of tricuspid annular plane systolic excursion (2.9 ± 0.1 vs. 4.0 ± 0.1 mm) and pulmonary artery acceleration time (24.3 ± 0.9 vs. 35.4 ± 1.8 ms) in SAB vs. sham rats. Nine weeks post SAB, left and right heart catheterization showed significant biventricular increases in end systolic and diastolic pressure in SAB vs. sham rats (LV: 226 ± 15 vs. 103 ± 5 mmHg, 34 ± 5 vs. 7 ± 1 mmHg; RV: 40 ± 4 vs. 22 ± 1 mmHg, and 4.7 ± 1.5 vs. 0.9 ± 0.5 mmHg, respectively). Picrosirius red staining showed marked biventricular fibrosis in SAB rats. There was increased muscularization of small pulmonary arteries in SAB rats. Confocal microscopy showed biventricular mitochondrial depolarization and fragmentation in SAB vs. sham cardiomyocytes. Transmission electron microscopy confirmed a marked biventricular reduction in mitochondria size in SAB hearts. Immunoblot showed marked biventricular increase in PKM2/PKM1 and MiD51 expression. Mitofusin 2 and mitochondrial pyruvate carrier 1 were increased in SAB LVs. Conclusions: SAB caused group 2 PH. Impaired RV function and RV fibrosis were associated with increases in mitochondrial fission and expression of MiD51 and PKM2. While these changes would be expected to promote increased production of reactive oxygen species and a glycolytic shift in metabolism, further study is required to determine the functional consequences of these newly described mitochondrial abnormalities.